An investigation on the management on the night market activity / Mohamad Zaid Mat Daud @ Yaacob - Mohamad Zaid Mat Daud @ Yaacob (Faculty of Architecture, Planning and Surveying, 2013)
Night market in Malaysia had been glamour destination among locals because it provides shopping alternative thing such as food, household requirement and other various clothing. The night market frequently reflected certain aspects of the Malaysian unique culture, especially local food, their people, the eating habits as well as the multiple of the population. The night market utilizes the concept of open space market place to night market activities. The local authority will provide stalls to traders, and traders will set up tents, tools, tables and other equipment to display and prepare their own products to buyers. In the dissertation it will discuss more about management in night market activities where these activities are carried out in the surrounding of the buildings or residential area. Beside that in this dissertation it will found usually problem occur in the management of night market activities. This dissertation finally comes out with rationale conclusion and recommendations were suitable to be implementing on night market activities to overcome the problem that there facing.